COVID-19 in Hospitalised Children and Adolescents: Review of the First Pandemic Year at Vilnius University Hospital Santaros Klinikos - Ivaškevičienė, Inga; Donielaitė – Anisė, Kamilė; Žilinskaitė, Virginija; Vaičiūnienė, Daiva; Ivaškevičius, Rimvydas (Acta medica Lituanica, 2022)
Background. Since the start of the pandemic with SARS-CoV-2 virus, very little data was known about clinical features and outcomes of COVID-19 in children and adolescents not only in Lithuania, but also in other European countries. This study was started in collaboration with 82 participating healthcare institutions across 25 European countries, using a well-established research network—the Paediatric Tuberculosis Network European Trials Group (ptbnet). This multinational, multicentre cohort study was performed during the first wave of the pandemic, between April 1 and April 24, 2020. Each participating country was allowed to continue further research individually encompassing brighter time limits and using the same methodology. We present here data of children hospitalised at Vilnius University Hospital Santaros Klinikos (VUH SK) during the first year of the pandemic. Materials and methods. We included all paediatric patients with PCR confirmed SARS-CoV-2 infection who were hospitalised at VUH SK. The study was performed between March 12, 2020 and March 12, 2021. A standardised data collection spreadsheet was used to record epidemiological, clinical and treatment data. Results. A total of 104 patients were included in the study. The median age of participants was 5 years (IQR 1.0-11.0, range 0-17 years). Males accounted for 50 (48%) of all patients. The average duration of hospitalisation was 3 days. Ten (9.6%) patients had pre-existing medical conditions. Among all hospitalised patients 16 (15%) were asymptomatic, 5 (4.8%) were treated in intensive care unit (ICU). The most common symptoms among COVID-19 patients were pyrexia 71 (68%) followed by upper respiratory tract infection 49 (47%) and gastrointestinal symptoms 33 (32%). Among the entire cohort only 3 (3%) patients required oxygen support, but none of them was started on continuous positive airway pressure (CPAP), mechanical ventilation or extracorporeal membrane oxygenation (ECMO). None of the patients admitted to ICU needed inotropic support. There was no fatal outcome. Conclusions. Our data indicate that COVID-19 may affect children of any age. The COVID-19 disease was usually mild in hospitalized children and adolescents. The most common clinical findings of COVID-19 were pyrexia and symptoms of upper respiratory tract infection. Severe COVID-19 disease cases when oxygen support or treatment in ICU was required were very rare. No patient received antiviral drugs for Covid-19 treatment. There was no fatal outcome due to COVID-19 in our study population.